2000
DOI: 10.1074/jbc.275.7.4640
|View full text |Cite
|
Sign up to set email alerts
|

The Low M r Protein-tyrosine Phosphatase Is Involved in Rho-mediated Cytoskeleton Rearrangement after Integrin and Platelet-derived Growth Factor Stimulation

Abstract: The low molecular weight protein-tyrosine phosphatase (LMW-PTP) is an enzyme that is involved in the early events of platelet-derived growth factor (PDGF) receptor signal transduction. In fact, LMW-PTP is able to specifically bind and dephosphorylate activated PDGF receptor, thus modulating PDGF-induced mitogenesis. In particular, LMW-PTP is involved in pathways that regulate the transcription of the immediately early genes myc and fos in response to growth factor stimulation. Recently, we have found that LMW-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
78
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 30 publications
3
78
1
1
Order By: Relevance
“…We have previously demonstrated that LMW-PTP exists in two different cellular pools: a cytosolic pool, which is recruited to the membrane upon PDGF stimulation acting directly on PDGF-R, and a second pool anchored to the cytoskeleton that acts on a different substrate, p190Rho-GAP (10). LMW-PTP is thus able to influence cell growth through PDGF-R dephosphorylation and cytoskeleton rearrangement through Rho regulation.…”
Section: Regulation Of Lmw-ptp Activity On Pdgf Receptor Duringmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated that LMW-PTP exists in two different cellular pools: a cytosolic pool, which is recruited to the membrane upon PDGF stimulation acting directly on PDGF-R, and a second pool anchored to the cytoskeleton that acts on a different substrate, p190Rho-GAP (10). LMW-PTP is thus able to influence cell growth through PDGF-R dephosphorylation and cytoskeleton rearrangement through Rho regulation.…”
Section: Regulation Of Lmw-ptp Activity On Pdgf Receptor Duringmentioning
confidence: 99%
“…Cytoskeleton-associated LMW-PTP influences cell adhesion, spreading, and migration, controlling the phosphorylation level of p190Rho-GAP, a protein that is able to regulate Rho activity and, consequently, cytoskeleton rearrangement in response to PDGF stimulation. Hence, LMW-PTP is able to perform multiple roles in PDGF-induced mitogenesis: while cytosolic LMW-PTP binds and dephosphorylates PDGF-R (4), thus modulating part of its signaling cascade, cytoskeleton-associated LMW-PTP acts on phosphorylated p190Rho-GAP, consequently play-ing a role in PDGF-mediated cytoskeleton rearrangement (10).…”
mentioning
confidence: 99%
“…The assay was performed as described elsewhere (Chiarugi et al, 2000). In brief, 96-well plates were coated with 30 mg/ml collagen type 1 (PromoCell, Heidelberg) at 41C overnight and washed twice with PBS.…”
Section: Cell Adhesion Assaymentioning
confidence: 99%
“…This reversible phosphorylation/dephosphorylation process is catalysed by opposing reactions of protein kinases and protein phosphatases (1,2). It has been well studied that in eukaryotes protein phosphorylation on tyrosine residues plays a key role in the regulatory mechanism of various cellular processes including growth, differentiation, cell cycle regulation and cytoskeletal function (3,4), and as well as controls many diseases (5,6) including infectious diseases (7,8). In comparison to eukaryotes, the occurrence of protein tyrosine kinases (PTKs)/protein tyrosine phosphatases (PTPs) in bacteria including photosynthetic cyanobacteria, was suggested much later (9 15).…”
mentioning
confidence: 99%